Polarization conversion-based molecular sensing using anisotropic plasmonic metasurfaces. Issue 20 (6th May 2016) - Verre, R.; Maccaferri, N.; Fleischer, K.; Svedendahl, M.; Odebo Länk, N.; Dmitriev, A.; Vavassori, P.; Shvets, I. V.; Käll, M.
Abstract : Using polarization rotation in plasmonic dimers we demonstrate a new sensing platform with a sensitivity comparable to the best optical biosensors. Abstract : Anisotropic media induce changes in the polarization state of transmitted and reflected light. Here we combine this effect with the refractive index sensitivity typical of plasmonic nanoparticles to experimentally demonstrate self-referenced single wavelength refractometric sensing based on polarization conversion. We fabricated anisotropic plasmonic metasurfaces composed of gold dimers and, as a proof of principle, measured the changes in the rotation of light polarization induced by biomolecular adsorption with a surface sensitivity of 0.2 ng cm −2 . We demonstrate the possibility of miniaturized sensing and we show that experimental results can be reproduced by analytical theory. Various ways to increase the sensitivity and applicability of the sensing scheme are discussed.